Hierarchical medical system and local medical performance: A quasi-natural experiment evaluation in Shanghai, China - Chen Liang; Yihang Zhao; Chenglong Yu; Peng Sang; Long Yang (Frontiers Media S.A., 2022)
BackgroundIn order to maintain high standards of healthcare, it is necessary for medical departments to provide high-quality and affordable medical services to local residents. This has been widely accepted in developed countries, while the medical treatment systems in developing countries remain to be improved. This research is based on a pilot of a hierarchical medical system in Shanghai, China, to evaluate the effects on policy of medical reform in developing countries.Methods and resultsBy means of the difference-in-differences (DID) method, the causal relationship between medical care services' improvement and hierarchical medical systems' implementation could be identified. This project also explores the differential effects of policy intervention and confirms that the pilot showed a significant improvement in medical performance in central districts while the result remains uncertain in terms of suburban districts. Furthermore, the dynamic effect of a hierarchical medical system has also been identified with the event study method, while the policy pilot only had short-term effects on local medical resources' improvement. In order to ascertain the function mechanisms of hierarchical medical systems and explain why the policy pilot only had short-term effects, this project also conducts influencing mechanism analysis with the triple-differences method (also known as difference-in-difference-in-differences or DDD method). According to the empirical results, there is no direct evidence indicating the hierarchical medical system could bring obvious benefits from the perspectives of patients and medical institutions.ConclusionsFor better implementation of hierarchical medical systems in the future, long-term supervision mechanisms should be given more attention in the enforcement process of hierarchical medical systems. At the same time, more safeguarding measures should be implemented, such as supervising the payment systems of the medical institution and conducting performance evaluation.